Obtaining oxide compounds of metals from water solution by contact non-equilibrium plasma treatment - Сергеева, Ольга Вячеславовна; Пивоваров, Александр Андреевич (Technology audit and production reserves, 2016)
The data obtained as the authors themselves with the assistance of laboratory equipment as well as data obtained from the literature, are used in the article. This study examined obtaining superfine powders of oxygen-containing compounds of cobalt and copper in the water solutions. The necessity of these studies due to the fact that the characteristics of the particles greatly depends on the production method, and, therefore, further studies were necessary for particles obtained by the treatment of water solutions by contact non-equilibrium plasma. When using the plasma chemical processing method for the Co(OH)2 in water and CuSO4 solution, sediments with dimensional characteristics in the range from 8 to 110 nm were obtained. Larger particles are shown in the form of agglomerates 0,5-5 microns. Sediments of cobalt compounds are presented in the form of β-form of cobalt hydroxide (II), CoO, Co3O4, and copper compounds in the form of Cu2O, CuO and Cu, which is confirmed by X-ray diffraction data. The possibility to control the process of synthesis of particles by adjusting its parameters was proved that thanks to its constructive design is straightforward and is advantage of this method along with the possibility of using very dilute solutions. These studies point to the prospect of using the particles with desired characteristics for the development of catalysts for chemical processes in the production of ceramics, and dyes, as well as industries, including the development of chemical current sources.